Microbiological and molecular detection of Mycoplasma bovis in milk samples from bovine clinical mastitis - Salina, Anelise [UNESP]; Timenetsky, Jorge; Barbosa, Maysa S.; Azevedo, Cristiane M.; Langoni, Helio [UNESP] (FapUNIFESP (SciELO), 2020)
The genus Mycoplasma includes more than 200 bacterial species that cause disease in animals. It is responsible for causing mastitis in bovines and may be related to other manifestations, such as arthritis and pneumonia in calves and heifers. The present study aimed to detect Mycoplasma bovis isolated from milk samples of bovine clinical mastitis, and to compare the isolation rates in two culture media: Hayflick and SP4. An initial screening was performed in order to detect the presence of the class Mollicutes in 1166 milk samples from clinical mastitis by the conventional Polymerase Chain Reaction (PCR) technique. According to the 1166 milk samples evaluated, 8.6% (100/1166) were positive to class Mollicutes. Regarding molecular analyses, 1.1% (13/1166) of conventional PCR for positive M. bovis was obtained and 0.9% (11/1166) in real-time PCR. The results of the microbiological culture of the 100 samples previously screened demonstrated that 6% (6/100) of colony growth have been developed when using the Hayflick medium, and 11% (11/100) when using the SP4 medium (including the positive on Hayflick medium). Concerning the 11 isolates obtained in the microbiological culture, conventional PCR confirmed M. bovis in nine of them, and two cultures were negative. In the phylogenetic analysis of the isolates, all of them were grouped in M. bovis and M. agalactiae clusters. The results confirmed the importance of the presence of M. bovis in the etiology of bovine clinical mastitis and reinforced the need for further studies to elucidate other Mycoplasma species that may be involved in bovine clinical mastitis in Brazil.
Keywords: Bovine mastitis; Cattle; Microbiology; Milk; Molecular detection; Mollicutes; Mycoplasma bovis; Mycoplasmosis; PCR